Interannual variations in river water content and distribution over the Laptev Sea between 2007 and 2011: The Arctic Dipole connection. Issue 20 (18th October 2014) - Thibodeau, Benoit; Bauch, Dorothea; Kassens, Heidemarie; Timokhov, Leonid A.
Abstract Five years of oxygen isotope and hydrological surveys reveal interannual variations in the inventory and distribution of river water over the Laptev Sea. In 2007, 2009, and 2010 relatively low amounts of river water (≤1500 km3) were found and were mostly located in the southeastern Laptev Sea. In 2008 and 2011, high amounts of river water (~1600 km3 and ~2000 km3) were found, especially in the central and northern part of the shelf, suggesting a northward export of this water. This temporal pattern is coherent with the summer Arctic Dipole index that was higher in 2008 and 2011. Our results suggest that the Arctic Dipole might influence the export of river water from the Laptev Sea. Moreover, the river water inventory in the Laptev Sea seems related to the freshwater content of the Arctic Ocean with a 2 years lag.